ANALYSIS OF THE EFFECT OF SERVICE QUALITY AND SCHOOL LOCATION ON STUDENT SATISFACTION AND ITS IMPACT ON STUDENT LOYALTY AT 32 JAKARTA SENIOR HIGH SCHOOL - Waliha, Siti (Dinasti Publisher, 2020)
This study aims to analyze the effect of Quality. Service, and School Location towards Student Loyalty through Satisfaction in XII grade students at SMA Negeri 32 Jakarta. The results of the study using primary data in the form of questionnaires to 274 class XII students at SMA Negeri 32 Jakarta using the Structural Equation Modeling (SEM) method showed that service quality and school location had a positive and significant effect on student satisfaction. There is a positive and significant influence between service quality and student satisfaction on student loyalty, while there is no influence between school location on student loyalty. Judging from the results of the SEM calculation analysis of service quality, and school location has an estimate coefficient of 0.48 or 48% of its effect on student satisfaction, while service quality has an estimate coefficient of 0.56 its influence on student loyalty, and satisfaction has an estimate coefficient of 0.44 influence. student loyalty, this shows that the quality of service, and good student satisfaction will increase student loyalty at SMA Negeri 32 Jakarta, and the better the quality of service will increase student satisfaction. The results showed that student satisfaction as an intervening variable could increase the relationship between service quality variables and student loyalty, but did not affect the relationship between school locations and loyalty